140k views
1 vote
Please help me out with this !!!!!!!

Please help me out with this !!!!!!!-example-1
User Litsa
by
5.2k points

1 Answer

1 vote

Answer:

y = 2x - 1

Explanation:

Consider the differences between consecutive values of y. If constant then this value is the multiplier.

1 - (- 1) = 3 - 1 = 5 - 3 = 7 - 5 = 9 - 7 = 2 ← constant difference, hence

y = 2x

Given the point (0, - 1 ) then we require to subtract - 1, that is

y = 2x - 1 ← equation relating x and y

User Minghan
by
5.3k points